Evaluating the Value for Money of Interventions to Support Behavior Change for Better Health (Behavior Change Evaluation Tools). (June 2013) - Lister, Graham; Merritt, Rowena
This article reports the development of tools for use by local commissioning teams, based in English Local Authorities (Local Government Councils), to evaluate the value for money of their behavior change investments. The national program was guided by a panel of senior advisers and included consultations with experts in the field, as the basis for the design of the methodology. Evaluation tools were then developed applying evidence provided by the National Institute for Health and Clinical Excellence, the World Health Organization, Health England (a national group set up to advise on public health policy), and other sources. As data were often incomplete, provision was made to update the tools as further evidence emerges. The tools, which are now available online athttp://www.thensmc.com/resources/vfm, cover: smoking cessation, alcohol harm reduction, obesity reduction, comprising, weight loss, diet and increased activity, breast feeding continuation, and participation in bowel cancer screening. The use of these tools by local teams has proved valuable in demonstrating the relative value for money of local interventions and the importance of further developments of this kind.